External training load and the effects on training response following three different training sessions in young elite beach volleyball players. Issue 5 (December 2020) - Pelzer, Thiemo; Schmidt, Marcus; Jaitner, Thomas; Pfeiffer, Mark
Purpose: The interaction between external training load (ETL) and players internal response in beach volleyball is currently poor investigated. Using single parameters (e.g. jump volume) described in indoor settings is questionable due to specific load characteristics like sandy ground and reduced number of players. The aim of this work is to analyze ETL and the effects on training response in different beach volleyball training settings. Methods: This study was conducted with 7 youth elite athletes (age: 18.9 ± 1.3 years, height: 185.2 ± 7 cm, body mass: 75.9 ± 10.4 kg, 2 males/5 females). Training sessions were classified into three categories with (A) high session jump volume (SJV) and lower proportions of other action types like diving, reception, defense actions and setting, (B) moderate SJV and (C) low SJV and higher proportions of other action types. Delayed Onset of Muscle Soreness [DOMS], Creatinkinase [CK] and session rate of perceived exertion [s-RPE] were analyzed as training response markers. Results: Mean pre to post differences in CMJ-Height were highest at sessions with high jump volume and less other actions (Session A) with no significant differences between (C) to (B) ( p = .128 ), (C) to (A) ( p = .237 ) and (B) to (A) ( p = .101 ). Response markers (DOMS, s-RPE, CK) showed increased values at session type C. Conclusions: SJV does not seem to trigger training response with higher marker responsiveness during low frequency sessions. Changes in directions, diving or fast getting up might rather provoke fatigue during training.